2020
DOI: 10.1186/s12934-020-01314-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial enhanced oil recovery through deep profile control using a conditional bacterial cellulose-producing strain derived from Enterobacter sp. FY-07

Abstract: Background: Heterogeneity of oil-bearing formations is one of major contributors to low oil recovery efficiency globally. Long-term water flooding will aggravate this heterogeneity by resulting in many large channels during the exploitation process. Thus, injected water quickly flows through these large channels rather than oil-bearing areas, which ultimately leads to low oil recovery. This problem can be solved by profile control using polymer plugging. However, non-deep profile control caused by premature pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The majority of the previous studies of FY-07 focused on the analyses of its unique BC production mechanism under anaerobic conditions [ 11 , 36 ], increasing the productivity [ 12 , 15 ] and expanding the application range of BC [ 13 , 14 , 35 , 37 ]. Herein, FY-07 was reclassified into the species oryzendophytica in the genus Kosakonia through a polyphasic approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the previous studies of FY-07 focused on the analyses of its unique BC production mechanism under anaerobic conditions [ 11 , 36 ], increasing the productivity [ 12 , 15 ] and expanding the application range of BC [ 13 , 14 , 35 , 37 ]. Herein, FY-07 was reclassified into the species oryzendophytica in the genus Kosakonia through a polyphasic approach.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of the taxonomy of Enterobacter , the genus Kosakonia was separated from the genus Enterobacter [ 1 ]. Thanks to its excellent BC production capacity and unique fermentation characteristics, FY-07 has been continuously researched and developed [ 11 , 12 , 13 , 14 , 15 ]. Comparative genomic analysis of a report suggested that FY-07 may be closely related to Kosakonia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity of the penetrating water is further increased using a mobility control agent to improve the oil sweep efficiency and the mobility stoichiometry by equalizing the permeability across the reservoir. The global capital market for biopolymers is anticipated to increase 17% and reach USD 10 billion by 2021 [116][117][118].…”
Section: Biopolymersmentioning
confidence: 99%
“…In a SP binary system, polymers have a vital influence on improving the viscosity of flooding fluids, changing the direction of water flow in formations, improving the volume sweep efficiency, and reducing the adsorption of the surfactant in the reservoir rock and ultimately enhancing oil recovery. Generally, synthesized polymers such as partially hydrolyzed polyacrylamide (HPAM) have been widely applied in commercial EOR projects benefiting from their good performances and low cost . Compared with synthetic polymers, the biopolymers produced by microorganisms inherit the characteristics of biocompatibility and biodegradation, making them capture much attention in the application of petroleum engineering .…”
Section: Introductionmentioning
confidence: 99%